Variability in oceanographic barriers to coral larval dispersal: Do currents shape biodiversity?. (July 2018) - Thompson, D.M.; Kleypas, J.; Castruccio, F.; Curchitser, E.N.; Pinsky, M.L.; Jönsson, B.; Watson, J.R.
Highlights: Reefs in the Coral Triangle are highly self-seeded. Reef connectivity in the Coral Triangle is highly variable from year to year. Dispersal simulations must be >20 years long to capture connectivity variability. Connectivity subpopulations illustrate physical oceanographic barriers to dispersal. Oceanographic barriers play an important role in shaping patterns of biodiversity. Abstract: The global center of marine biodiversity is located in the western tropical Pacific in a region known as the "Coral Triangle" (CT). This region is also considered the most threatened of all coral reef regions, because multiple impacts, including rising temperatures and coral bleaching, have already caused high mortality of reef corals over large portions of the CT. Larval dispersal and recruitment play a critical role in reef recovery after such disturbances, but our understanding of reproductive connectivity between reefs is limited by a paucity of observations. Oceanographic modeling can provide an economical and efficient way to augment our understanding of reef connectivity, particularly over an area as large as the CT, where marine ecosystem management has become a priority. This work combines daily averaged surface current velocity and direction from a Regional Ocean Modeling System developed for the CT region (CT-ROMS) with a Lagrangian particle tracking tool (TRACMASS) to investigate the probability of larval transport between reefs for a typical broadcasting coral. A 47-year historical simulation (1960–2006) was used to analyze the potential connectivity, the physical drivers of larval transport, and its variability following bi-annual spawning events in April and September. Potential connectivity between reefs was highly variable from year to year, emphasizing the need for long simulations. The results suggest that although reefs in this region are highly self-seeded, comparatively rare long-distance dispersal events may play a vital role in shaping regional patterns of reef biodiversity and recovery following disturbance. The spatial pattern of coral "subpopulations, " which are based on the potential connectivity between reefs, agrees with observed regional-scale patterns of biodiversity, suggesting that the physical barriers to larval dispersal are a first-order driver of coral biodiversity in the CT region. These physical barriers persist through the 21st Century when the model is forced with the Community Earth System Model (CESM) RCP8.5 climate scenario, despite some regional changes in connectivity between reefs.